Phytochemical Evaluation and Antioxidant-Antimicrobial Potential of Lilium spp. Bulbs: Therapeutic and Dermatocosmetic Applications - Simona Lupșor; Gabriela Stanciu; Radu Emilian Cristache; Emilia Pănuș; Cristiana Radulescu; Radu Lucian Olteanu; Claudia Lavinia Buruleanu; Raluca Maria Stirbescu (Plants, 2025)
Lilium spp. bulbs are traditionally valued for their medicinal properties, yet their phytochemical profile and biomedical potential remain underexplored. This study aims to assess the antioxidant, antimicrobial, and dermatocosmetic potential of ethanolic macerates from five Lilium spp. cultivars. Bulb macerates were obtained using 70% and 96% ethanol and evaluated for total phenolic content (TPC), total flavonoid content (TFC), condensed tannins (CTC), mineral composition, and antioxidant activity (DPPH assay). Spectroscopic (FTIR) and antimicrobial analyses were also performed. Macerates from Lilium “Dark Secret” (LD-70) and Lilium asiaticum “White” (LA-70) exhibited the highest levels of TPC (225 and 162.5 mg GAE/100 g f.w.), TFC (26.12 and 21.75 mg QE/100 g f.w.), and antioxidant activity (81.5 and 58.75 mg GAE/100 g f.w.). FTIR confirmed the phenolic composition, while mineral analysis revealed a high potassium content and negligible toxic metals. Selective antimicrobial activity was observed against Escherichia coli, Pseudomonas aeruginosa, and Candida albicans, particularly for LD-70 and LA-70 macerates. Based on these findings, stable hydrogel formulations incorporating LD-70 and LA-70 were developed, showing favorable pH, rheology, and sustained antioxidant activity over 60 days. These findings support the integration of Lilium-derived macerates into dermatocosmetic formulations targeting skin protection and microbial defense.